Fathering the Nation : American Genealogies of Slavery and Freedom. - Castronovo, Russ (UC Press voices revived., 2022)
Russ Castronovo underscores the inherent contradictions between America's founding principles of freedom and the reality of slavery in a book that probes mid-nineteenth-century representations of the founding fathers. He finds that rather than being coherent and consensual, narratives of nationhood are inconsistent, ambivalent, and ironic. He examines competing expressions of national memory in a wide range of mid-nineteenth-century artifacts: slave autobiogra.